Fear of Missing Out (FoMo) Tendencies Among Student Residents - Eva Imania Eliasa; Muthi’ Azmiatin Hasanah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
Emerging adulthood is marked by a lot happening within it and its environment. Plus, the rapid development of technology makes the world at hand. This situation triggers FoMO in individuals, including students. This study aims to identify the prevalence of FoMO among students living in the Mujahidin Mosque Women's Dormitory at Yogyakarta State University. This study uses a quantitative approach with quantitative descriptive analysis. The participants in this study were all residents of the Mujahidin Mosque women's dormitory, totaling 75 female students, and the study used a total sampling technique. The research findings indicate that the respondents' Fear of Missing Out (FoMO) tendency predominantly falls into the low category, with 32 respondents, or approximately 42.7% of the total respondents. However, some students who exhibit FoMO tendencies at moderate levels, totaling 19 respondents (25.3%), while 15 individuals (20%) fall into the high category, and 7 respondents (9.3%) are classified under the very high category.